2023
DOI: 10.1111/gcbb.13098
|View full text |Cite
|
Sign up to set email alerts
|

Climate cooling benefits of cellulosic bioenergy crops from elevated albedo

Cheyenne Lei,
Jiquan Chen,
G. Philip Robertson

Abstract: Changes in land surface albedo can alter ecosystem energy balance and potentially influence climate. We examined the albedo of six bioenergy cropping systems in southwest Michigan USA: monocultures of energy sorghum (Sorghum bicolor), switchgrass (Panicum virgatum L.), and giant miscanthus (Miscanthus × giganteus), and polycultures of native grasses, early successional vegetation, and restored prairie. Direct field measurements of surface albedo (αs) from May 2018 through December 2020 at half‐hourly intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…Conversely, miscanthus PPFD i remained high until harvest. These results agree with previous studies in the US Midwest that show greater albedo and PPFD i values for miscanthus relative to other crops (Dohleman & Long, 2009;Heaton et al, 2008;Lei et al, 2023;Miller et al, 2016;Moore et al, 2021).…”
Section: Solar Radiation Balancesupporting
confidence: 92%
See 1 more Smart Citation
“…Conversely, miscanthus PPFD i remained high until harvest. These results agree with previous studies in the US Midwest that show greater albedo and PPFD i values for miscanthus relative to other crops (Dohleman & Long, 2009;Heaton et al, 2008;Lei et al, 2023;Miller et al, 2016;Moore et al, 2021).…”
Section: Solar Radiation Balancesupporting
confidence: 92%
“…While our measurements support our hypothesis, Hickman et al (2010) in Illinois showed no differences in R n and G between miscanthus and corn, which implies that the crops had similar AE in their study. Reports by Miller et al (2016), Moore et al (2021), and Lei et al (2023) showed that miscanthus had greater albedo than corn, but these authors did not demonstrate whether it affected R n or AE. We are not aware of other current studies that attempted to evaluate R n and AE differences between miscanthus and corn (or any other row crop).…”
Section: Surface Energy Balancementioning
confidence: 90%
“…These imbalances due to surface albedo changes are referred to as albedoinduced radiative forcing (RF α ). The RF from albedo difference is the amount of energy reflected for assessing the warming/cooling potentials of different surfaces (Lei 2022, Lei et al 2023. However, to gauge the cooling potential of agricultural surfaces, the analysis of the variability and dynamics of albedo across unique landscapes needs to be performed at multiple temporal scales and at different crop types.…”
Section: Introductionmentioning
confidence: 99%
“…Still, current scientific understanding of forcing effects of albedo is relatively low (IPCC 2022, Sciusco et al 2022. Previous studies have attempted to bridge this knowledge gap using satellite data (Fang et al 2007, Zhang et al 2010, Sciusco et al 2020, 2022, where spatial measurements are effective but discontinuous temporal measurements may miss key crop phenological stages; or by using biophysical models (Smith et al 2020), where albedo is often estimated by generic values not representative of individual crops on the land surface. In contrast, field-based observations can be employed to more accurately observe changes in phenology, document unique agronomic managements over the course of a growing season, and identify crop-specific surface reflectivity benefits not easily discerned from satellite pixels.…”
Section: Introductionmentioning
confidence: 99%